A THEOLOGY OF THE CHURCH FOR THE FUTURE: A PARTICIPATORY CHURCH OF EQUAL DISCIPLESHIP - Kochuthara, Shaji George (Asian Horizons, 2015)
Even after fifty years, the Second Vatican Council inspires us to build up a more participatory Church of equal discipleship. This paper, beginning with an overview of the pre-Vatican II ecclesiology, shows how the Second Vatican Council brought about revolutionary changes in the theology of the Church. Following this, the paper points out a few areas where changes might be required for becoming a more participatory Church. It is argued that we need a Church free of clericalism, a Church which is more participatory and democratic. Only if the faithful get the opportunity for active participation in the life of the Church they will have a sense of belongingness. The process undertaken by the two sessions of the Synod on the Family gives the hope that the participatory model can still prevail in the Church. Similarly, the Church of the future should ensure equal discipleship of men and women. In spite of the recognition in theory of the equal dignity of women, in practice, women continue to be discriminated.The Church should ensure that women receive equal opportunities to work for the good of the community and glory of God as equal partners.